Operation optimization of holding furnaces in special casting shops - Dotsenko, Yuri; Dotsenko, Nataliia; Tkachyna, Yevhenii; Fedorenko, Vadym; Tsybulskyi, Yevhenii (Technology audit and production reserves, 2018)
The object of research is the melting and casting system of special casting shops. The process is considered on the basis of simulation modeling of the requirements of chill or melts pressure casting machines and the capabilities of the melting and holding furnaces to meet this need. The modeling is carried out on the basis of typical solutions for the used brands of furnaces for the manufacture of aluminum alloys in non-ferrous casting shops of a machine-building enterprise specializing in the manufacture of casting in metal molds for engineering products. As a result of simulation modeling, a description is obtained of the influence of the intensity of applications on the melt on the part of chill machines or injection molding machines, and the time taken to complete these applications for the total costs of the implementation of the technological process. It is proposed to determine the total costs as the sum of the costs associated with the consumption of technological electricity, and the costs associated with the likely downtime of machines due to lack of metal. Moreover, the second component reflects the requirement for the performance of machines in terms of their actual operation. Therefore, the total cost of the process of chill casting or casting under pressure in terms of the consistency of the elements of the melting and casting system is chosen as the criterion for optimizing its operation. It is proposed to consider the melting and casting system as a queuing system (QS) with failures. Such a presentation is the most stringent in terms of requirements for ensuring a given performance. Using the study of the response surface, the optimization problem is solved according to the consistency of the intensity of requests for the melt and the time of their execution, which minimizes the total costs of the implementation of the technological process. Local optimal technological solutions are obtained that enable technologists to choose the most rational decisions for conducting a melting campaign using transfer furnaces with a capacity of 0.16–0.25 tons. Such solutions will provide the possibility of reducing the cost of manufacturing aluminum casting.